1996
DOI: 10.1093/brain/119.3.815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic stimulation over supplementary motor area on movement in Parkinson's disease

Abstract: Movement execution can be delayed by transcranial magnetic stimulation delivered over primary motor cortical areas, resulting in transient inhibition of cortico-motor output. Inhibition or disruption of higher-order motor planning and preparatory processes, such as are thought to occur in the supplementary motor area (SMA), would allow an examination of processes at other stages of the motor control system. In this study, six subjects with Parkinson's disease and six healthy control subjects performed a non-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 32 publications
2
40
1
1
Order By: Relevance
“…Finding SMA to be particularly engaged during this task, our results are in line with results from patient studies indicating the SMA to subserve anticipatory postural control associated with a voluntary limb movement (Gurfinkel and Elner, 1973;Wiesendanger et al, 1973;Wiesendanger, 1981;Massion and Dufosse, 1988;Massion et al, 1989;Massion, 1992). Anticipatory postural adjustments, which are subserved by SMA, precede and accompany most movements, particularly bilateral ones, thus establishing the role of the SMA in the preparation of movement in general (Brinkman, 1984;Cunnington et al, 1996). The present findings add to this account, showing SMA to be particularly activated by the attentive observation of hip and shoulder motion of another person.…”
Section: Discussionsupporting
confidence: 74%
“…Finding SMA to be particularly engaged during this task, our results are in line with results from patient studies indicating the SMA to subserve anticipatory postural control associated with a voluntary limb movement (Gurfinkel and Elner, 1973;Wiesendanger et al, 1973;Wiesendanger, 1981;Massion and Dufosse, 1988;Massion et al, 1989;Massion, 1992). Anticipatory postural adjustments, which are subserved by SMA, precede and accompany most movements, particularly bilateral ones, thus establishing the role of the SMA in the preparation of movement in general (Brinkman, 1984;Cunnington et al, 1996). The present findings add to this account, showing SMA to be particularly activated by the attentive observation of hip and shoulder motion of another person.…”
Section: Discussionsupporting
confidence: 74%
“…This hypothesis was based on clinical speculation (Morris 2000;Morris et al, 1997), in addition to the literature which has demonstrated impaired anticipatory postural control during arm movements while standing in PD subjects (Latash et al 1994;Rogers et al 1987;Traub et al 1980). Furthermore, several studies have shown altered function of the supplementary motor area in PD due to its indirect connections with the basal ganglia (Cunnington et al 1996;Grafton et al 1995). The supplementary motor is one structure thought to have a major role with the preparation of movement (Brinkman 1984;Cunnington et al 1996) and also specifically with anticipatory postural adjustments (Massion 1992;Massion et al 1989).…”
Section: Altered Movement Strategymentioning
confidence: 99%
“…Furthermore, several studies have shown altered function of the supplementary motor area in PD due to its indirect connections with the basal ganglia (Cunnington et al 1996;Grafton et al 1995). The supplementary motor is one structure thought to have a major role with the preparation of movement (Brinkman 1984;Cunnington et al 1996) and also specifically with anticipatory postural adjustments (Massion 1992;Massion et al 1989). However, our results did not support the hypothesis that individuals with PD do not move their COM adequately over the base of support prior to lift-off.…”
Section: Altered Movement Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the subcortically driven internal timing cues via the SMA to facilitate the initiation of movement, Cunnington et al (1996) suggested that the lateral premotor -cerebellar route provides external timing cues to compensate for deficient internal cues from the basal ganglia to the SMA. This could explain why external feedback systems e.g.…”
Section: Resultsmentioning
confidence: 99%